Information technology, change and information professionals' identity construction: A discourse analysis. Issue 1 (2014) - Hicks, Deborah
ABSTRACT: Information and communication technologies (ICTs) are often identified by librarians and information professionals as being a driving force behind the way they perform their day‐to‐day activities and how they interact with their clients. This study considers the role ICTs play in the shaping and constructing of the identities of librarians. Using data gathered from interviews, email discussion lists, and the professional literature, this study employed a discourse analysis to examine the language resources librarians use when constructing their professional identities, with particular attention to the role of ICTs in this construction. ICTs both challenged and enhanced the identities of librarians. While the changes related to ICTs have left librarians feeling insecure about their professional positions, they have also opened up new roles and opportunities for librarians to pursue. Librarians have a service‐oriented identity that is influenced by ICT‐related changes affecting their work. These changes will challenge and benefit librarians as they engage with ICTs and determine how, if at all, they can be incorporated into their day‐to‐day practice.